RED, PEF, and EPD: Conflicting rules for determining the carbon footprint of biofuels give unclear signals to fuel producers and customers - Brandão, Miguel; Ekvall, Tomas; Poulikidou, Sofia; Johansson, Kristin; Nilsson, Johan; Nojpanya, Pavinee; Wikström, Anna; Rydberg, Tomas (Frontiers in Climate, 2022)
Biofuel producers and other commodity suppliers are increasingly affected by conflicting rules for life cycle assessment (LCA). They may get multiple requests for LCAs to be used in various contexts, which require the application of different methodological approaches that vary in scope, system boundaries, data demand and more. This results in increased cost and competence requirements for producers, as well as confusion among other actors including their customers. Differences in methodologies might also lead to various outcomes, conclusions and conflicting guidance regarding which fuels to prioritize or develop. We have analysed the actual differences when applying three different frameworks: the EU Renewable Energy Directive (RED), the EU framework for Product Environmental Footprints (PEF), and the framework of Environmental Product Declarations (EPD), which have different modelling requirements. We analysed the methods from a conceptual point of view and also applied the methods to estimate the carbon footprint on a wide range of biofuel production pathways: i) ethanol from corn, ii) fatty acid methyl ester (FAME) from rapeseed oil, iii) biogas from food waste, iv) hydrogenated vegetable oil (HVO) from rapeseed oil and v) HVO from used cooking oil. Results obtained for a specific fuel could differ substantially depending on the framework applied and the assumptions and interpretations made when applying the different frameworks. Particularly, the results are very sensitive to the modelling of waste management when biofuel is produced from waste. Our results indicate a much higher climate impact for, e.g., biogas and HVO produced from used cooking oil when assessed with the PEF framework compared to the other frameworks. This is because PEF assigns at least part of the production of primary materials and energy to the use of recycled material and recovered energy. Developing Category Rules for biofuels for PEF and EPD ought to help clarifying remaining ambiguities.